The proportionality of decision taken to sign the AL-Ayadi residential investment project within the Hittin neighborhood in Baghdad by Urban filling style (Journal of Planner and Development, 2020)
This research will deal in a simple way with the concept of urban expansion and taking the decision to sign the spatial signature of residential investment projects in order to reach through them in a real way to the extent of the proportionality of the decision taken, in light of the fulfillment of the conditions that must be met in the matter of making the decision of the spatial signature of the residential investment project and the extent of commitment to them, in which the conditions are: (Ease of access to services and transportation, adequacy of services, commitment to urban land uses) when establishing the investment project represented by the Al-Ayad residential project in the Hittin neighborhood of Al-Karkh in Baghdad belonging to the municipality of Al-Mansour, and the axes of spatial influence in it, which are summarized by: the axis of land use, the axis of housing and population, the axis The economic aspect, the road services axis, the community services axis (health and education), the focus structures services (water supply service, sewage service, electricity services) and the environmental axis and finally the political axis by adopting the results of a survey of a sample of experts working in the Baghdad Municipality who are of a degree Director of the department upwards, and reached through it indicators that were adopted in the SWOT analysis of the study area under the assumption of the researcher D (50% of the residents of the residential investment project are from the study area), and thus this will lead to knowing the extent to which the decision taken is appropriate, with the proposal that the research is derived from the researcher’s unpublished master’s thesis.